Spider fauna (Arachnida, Araneae) in Mordovia State Nature Reserve and National Park “Smolny” (Russia) - Sergei Esyunin; Oksana Agafonova; Alexander Ruchin; Gennadiy Semishin; Mikhail Esin; Oleg Artaev (Biodiversity Data Journal, 2023)
Ecosystems in protected areas are richer in animal and plant species diversity ("biodiversity hotspots") due to more stringent conservation conditions. Of particular importance is scientific research and monitoring of this diversity in such areas. The aim of this study is to describe a set of data on Araneae occurrence in two protected areas: Mordovia State Nature Reserve and National Park "Smolny".About 29,000 individuals are identified to the species level. In total, 342 species were recorded for both PAs. The greatest species diversity was recorded in the families Linyphiidae (109 species; 32%), Lycosidae (38 species; 11%) Gnaphosidae (28 species; 8%), Araneidae (25 species; 7%), Salticidae (24 species; 7%), Thomisidae (23 species; 7%) and Theridiidae (22 species; 6% from total species diversity). The five species most abundant in the lower stratum (litter and moss layer) of biocenoses were Diplocephalus picinus, Microneta viaria, Tenuiphantes tenebricola, Diplostyla concolor and Abacoproeces saltuum and the five species most abundant in the vegetative stratum (herb, shrub and tree stems and canopy) were Linyphia triangularis, Enoplognatha ovata, Evarcha falcata, Misumena vatia and Evarcha arcuata. The dataset contains information on the occurrence of seven rare species (Centromerus nurgush, Centromerus persimilis, Diplocephalus dentatus, Entelecara flavipes, Metapanamomops kaestneri, Pelecopsis radicicola and Porrhomma microcavense), three species (Agalenatea redii, Neoscona adianta, Thanatus oblongiusculus) that entered here from the steppe zone and two synanthropic species (Steatoda castanea, Tegenaria domestica).